In support of researching later-life language variation and change - Pichler, Heike (Journal of Language and Aging Research, 2023)
Variationist sociolinguists must commit to developing age-comprehensive theories of sociolinguistic variation and lifespan change. They must extend analyses of patterns of language variation and change to include the oft-neglected later life-course, and must embrace cross-disciplinary knowledge exchange to identify and explore those ageing-associated biological, psychological and social changes that may impact language use in later life. Improved understanding of later-life linguistic diversity and instability will enhance current sociolinguistic theorizing and potentially also provide hypotheses about factors impacting language use in the early life-course. It will promote a richer understanding of the extent and interconnectedness of behaviour changes in later life. And it will also benefit the community of older adult language users by celebrating them as competent and agentive language users.